Rpv2 is part of a cluster of NLRs specific to Vitis rotundifolia and confers total resistance to grapevine downy mildew - Laurie Marsan; Emilce Prado; Sabine Wiedemann-Merdinoglu; Laure Schmidlin; Sophie Blanc; Marion Delame; Sylvain Schnee; Burak Arti; Guillaume Barnabé; Amandine Velt; Vincent Dumas; Didier Merdinoglu; et al. (Theoretical and Applied Genetics, 2025)

Allele-based modeling to predict phenological stages of grapevine hybrids under future climatic conditions - Elsa Chedid; Vincent Dumas; Komlan Avia; Didier Merdinoglu; Éric Duchêne (Theoretical and Applied Genetics, 2025)

Genetic diversity and population structure in Vitis species illustrate phylogeographic patterns in eastern North America - Jean‐Pierre Péros; Peter Cousins; Amandine Launay; Philippe Cubry; Andy Walker; Emilce Prado; Elisa Peressotti; Sabine Wiedemann‐Merdinoglu; Valérie Laucou; Didier Merdinoglu; Patrice This; Jean‐Michel Boursiquot; et al. (Molecular Ecology, 2021)
Geographical distribution and diversity of current plant species have been strongly shaped by climatic oscillations during the Quaternary. Analysing the resulting divergence among species and differentiation within species is crucial to understand the evolution of taxa like the Vitis genus, which provides very useful genetic resources for grapevine improvement and might reveal original recolonization patterns due to growth habit and dispersal mode. Here, we studied the genetic structure in natural populations of three species from eastern North America: Vitis aestivalis , V. cinerea and V. riparia using different marker types. Vitis aestivalis and V. cinerea showed higher diversity than V. riparia . The two former species are less differentiated, confirming an earlier divergence of V. riparia . V. aestivalis and V. riparia exhibited different genetic groups on both sides of the Appalachian Mountains that could mirror different recolonization routes from southern refugia. Genetic structure was stronger in V. cinerea , for which two varieties (var. berlandieri and var. cinerea ) are morphologically recognized. Our results confirm this distinction and suggest the existence of three other lineages within var. cinerea . These discontinuities appear linked to adaptation of var. berlandieri to dry and limy areas of Texas and partially to the Mississippi River Valley. Rapid range expansions from refugia upon climate warming are also suggested by the low linkage disequilibrium values observed. Furthermore, large variation for downy mildew resistance was observed in the three species. Our findings appeared consistent with the vegetation history of eastern North America.

Genetic variations of acidity in grape berries are controlled by the interplay between organic acids and potassium - Éric Duchêne; Vincent Dumas; Gisèle Butterlin; Nathalie Jaegli; Camille Rustenholz; Aurélie Chauveau; Aurélie Bérard; Marie Christine Le Paslier; Isabelle Gaillard; Didier Merdinoglu (Theoretical and Applied Genetics, 2020)

Introgression reshapes recombination distribution in grapevine interspecific hybrids - Marion Delame; Emilce Prado; Sophie Blanc; Guillaume Robert-Siegwald; Christophe Schneider; Pere Mestre; Camille Rustenholz; Didier Merdinoglu (Theoretical and Applied Genetics, 2019)

Quantitative trait loci affecting pathogen resistance and ripening of grapevines - Eva Zyprian; Iris Ochßner; Florian Schwander; Silvio Šimon; Ludger Hausmann; Martina Bonow-Rex; Paula Moreno-Sanz; Maria Stella Grando; Sabine Wiedemann-Merdinoglu; Didier Merdinoglu; Rudolf Eibach; Reinhard Töpfer (Molecular Genetics and Genomics, 2016)

A reference genetic map of Muscadinia rotundifolia and identification of Ren5, a new major locus for resistance to grapevine powdery mildew - Sophie Blanc; Sabine Wiedemann-Merdinoglu; Vincent Dumas; Pere Mestre; Didier Merdinoglu (Theoretical and Applied Genetics, 2012)

A standardised method for the quantitative analysis of resistance to grapevine powdery mildew - Anne-Sophie Miclot; Sabine Wiedemann-Merdinoglu; Eric Duchêne; Didier Merdinoglu; Pere Mestre (European Journal of Plant Pathology, 2012)

Towards the adaptation of grapevine varieties to climate change: QTLs and candidate genes for developmental stages - Eric Duchêne; Gisèle Butterlin; Vincent Dumas; Didier Merdinoglu (Theoretical and Applied Genetics, 2012)

Construction of a reference linkage map of Vitis amurensis and genetic mapping of Rpv8, a locus conferring resistance to grapevine downy mildew - Paule Blasi; Sophie Blanc; Sabine Wiedemann-Merdinoglu; Emilce Prado; Ernst H. Rühl; Pere Mestre; Didier Merdinoglu (Theoretical and Applied Genetics, 2011)

An extensive study of the genetic diversity within seven French wine grape variety collections - Frédérique Pelsy; Stéphanie Hocquigny; Ximena Moncada; Gérard Barbeau; Dominique Forget; Patricio Hinrichsen; Didier Merdinoglu (Theoretical and Applied Genetics, 2010)

Resistance to Plasmopara viticola in grapevine ‘Bianca’ is controlled by a major dominant gene causing localised necrosis at the infection site - Diana Bellin; Elisa Peressotti; Didier Merdinoglu; Sabine Wiedemann-Merdinoglu; Anne-Françoise Adam-Blondon; Guido Cipriani; Michele Morgante; Raffaele Testolin; Gabriele Di Gaspero (Theoretical and Applied Genetics, 2009)

Genetic dissection of sex determinism, inflorescence morphology and downy mildew resistance in grapevine - Elisa Marguerit; Christophe Boury; Aurélie Manicki; Martine Donnart; Gisèle Butterlin; Alice Némorin; Sabine Wiedemann-Merdinoglu; Didier Merdinoglu; Nathalie Ollat; Stéphane Decroocq (Theoretical and Applied Genetics, 2009)

A grapevine (Vitis vinifera L.) deoxy-d-xylulose synthase gene colocates with a major quantitative trait loci for terpenol content - Eric Duchêne; Gisèle Butterlin; Patricia Claudel; Vincent Dumas; Nathalie Jaegli; Didier Merdinoglu (Theoretical and Applied Genetics, 2009)

Structural variability of Tvv1 grapevine retrotransposons can be caused by illegitimate recombination - Cédric Moisy; Sophie Blanc; Didier Merdinoglu; Frédérique Pelsy (Theoretical and Applied Genetics, 2008)

Bread, beer and wine: Saccharomyces cerevisiae diversity reflects human history - JEAN‐LUC LEGRAS; DIDIER MERDINOGLU; JEAN‐MARIE CORNUET; FRANCIS KARST (Molecular Ecology, 2007)
Fermented beverages and foods have played a significant role in most societies worldwide for millennia. To better understand how the yeast species Saccharomyces cerevisiae , the main fermenting agent, evolved along this historical and expansion process, we analysed the genetic diversity among 651 strains from 56 different geographical origins, worldwide. Their genotyping at 12 microsatellite loci revealed 575 distinct genotypes organized in subgroups of yeast types, i.e. bread, beer, wine, sake. Some of these groups presented unexpected relatedness: Bread strains displayed a combination of alleles intermediate between beer and wine strains, and strains used for rice wine and sake were most closely related to beer and bread strains. However, up to 28% of genetic diversity between these technological groups was associated with geographical differences which suggests local domestications. Focusing on wine yeasts, a group of Lebanese strains were basal in an F ST tree, suggesting a Mesopotamia‐based origin of most wine strains. In Europe, migration of wine strains occurred through the Danube Valley, and around the Mediterranean Sea. An approximate Bayesian computation approach suggested a postglacial divergence (most probable period 10 000–12 000 bp ). As our results suggest intimate association between man and wine yeast across centuries, we hypothesize that yeast followed man and vine migrations as a commensal member of grapevine flora.

Anchoring of a large set of markers onto a BAC library for the development of a draft physical map of the grapevine genome - Didier Lamoureux; Anne Bernole; Isabelle Le Clainche; Sarah Tual; Vincent Thareau; Sophie Paillard; Fabrice Legeai; Carole Dossat; Patrick Wincker; Marilyn Oswald; Didier Merdinoglu; Céline Vignault; et al. (Theoretical and Applied Genetics, 2006)

Sampling strategy in molecular microbial ecology: influence of soil sample size on DNA fingerprinting analysis of fungal and bacterial communities - Lionel Ranjard; David P. H. Lejon; Christophe Mougel; Lucie Schehrer; Didier Merdinoglu; Rémi Chaussod (Environmental Microbiology, 2003)
Summary Assessing soil microbial community structure by the use of molecular techniques requires a satisfactory sampling strategy that takes into account the high microbial diversity and the heterogeneous distribution of microorganisms in the soil matrix. The influence of the sample size of three different soil types (sand, silt and clay soils) on the DNA yield and analysis of bacterial and fungal community structure were investigated. Six sample sizes from 0.125 g to 4 g were evaluated. The genetic community structure was assessed by automated ribosomal intergenic spacer analysis (A‐RISA fingerprint). Variations between bacterial (B‐ARISA) and fungal (F‐ARISA) community structure were quantified by using principal component analysis (PCA). DNA yields were positively correlated with the sample size for the sandy and silty soils, suggesting an influence of the sample size on DNA recovery, whereas no correlation was observed in the clay soil. B‐ARISA was shown to be consistent between the different sample sizes for each soil type indicating that the sampling procedure has no influence on the assessment of bacterial community structure. On the contrary for F‐ARISA profiles, strong variations were observed between replicates of the smaller samples (